Perceived Learning Environment: A Case of BBA Program at Dhankuta Multiple Campus - Parajuli, Kewal Ram; Pradhan, Khagendra; Kafle, Deepsikha (Journal of Research and Development, 2023)
Reinvigorating institutions and students in today's competitive global academic and industrial marketplace requires an assessment of the perceived learning environment. Students' academic performance, engagement and success is determined by students' perceived learning environment and academic management from an organization. Descriptive research design is used for the cross-sectional survey study and FGD was organized to assess the perceived learning environment and to compare by gender from students of Dhankuta Multiple Campus, Dhankuta, Nepal. Out of a total of 67 students of the BBA program 35 students have responded through Google from (DREEM Inventory) shared by researchers and 9 students were taken for FGD to find out their perceived environment and learning experiences in the existing environment. It is found that perception on the many aspects among 50 items on the existing environment are more positive than negative. Many aspects of campus learning environment needs to improve. There are insufficient physical facilities at classroom buildings and at hostel as students' need and expectation.